Pendampingan Pelaku UMKM untuk Optimalisasi Harga Jual Produk - Liza Novietta; Ruswan Nurmadi; Kersna Minan (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
MSMEs are part of the national economy that is self-reliant and has great potential to improve people's welfare. MSMEs have a significant role in the country's economic growth. The biggest problem is how SMEs can survive, compete and develop because it is related to the achievement of profits and the need for business capital. In order to achieve business goals, MSME actors must pay attention to the optimal selling price of their products. The selling price of products that are too low or too high will make profit not maximized, or will even result in losses. Forum Akademisi dan Praktisi Desa (FAPDes), where Universitas Harapan Medan is one of Education Institutions/University that joins it, provides assistance for Village Superior Products to MSME actors. It is hoped that in the future MSME actors who receive assistance can develop their businesses and excel compete with similar businesses or industries.Keywords: MSMEs, Selling Price, Profit